Application of amorphous silica nanoparticles in improving the rheological properties, filtration and shale stability of glycol-based drilling fluids. (June 2020) - Keshavarz Moraveji, Mostafa; Ghaffarkhah, Ahmadreza; Agin, Farough; Talebkeikhah, Mohsen; Jahanshahi, Amirhosein; Kalantar, Alireza; Amirhosseini, Saman Fazel; Karimifard, Mohsen; Mortazavipour, Seyed Iman; Sehat, Ali Akbari; Arjmand, Mohammad
Abstract: The drilling process in shale formations and well stability in the presence of shale are among the most challenging issues in the drilling industry. Routinely, oil-based drilling fluids are used for drilling troublesome shale formations. However, oil-based drilling muds have a number of significant disadvantages, including very high cost, causing severe damage to the environment, and interfering with the well-logging process. To address this issue, a sustainable glycol-based drilling fluid is designed in this study to substitute the routinely used oil-based drilling fluids. In the first step, amorphous silica nanoparticles with different particle sizes (12, 22, and 54 nm) are prepared from rice husks. The prepared nanoparticles are then dispersed in water and added to the glycol-based mud as a liquid-based additive. Finally, the effect of silica nanoparticles on rheological properties, filtration, and shale stability of glycol drilling fluid is studied. The results show that the use of silica nanoparticles improves the rheological properties of glycol drilling fluid. This improvement is a function of the amount and size of nanoparticles. Adding silica nanoparticles also decreases fluid loss and increases the thermal stability of the drilling fluid. Moreover, silica nanoparticles can effectively plug nanoscale pores of Gurpi shale resulting in increasing the shale cutting recovery and decreasing the penetration rate of glycol drilling fluid into the Gurpi shale samples.